Filming the end of the Holocaust : allied documentaries, Nuremberg and the liberation of the concentration camps - Michalcyzk, John J. (War, culture and society, 2016)
Introduction -- Prelude to Nuremberg : the Allies seek justice -- The US Signal Corps encounters atrocities -- The British liberation of Bergen-Belsen : memory of the camps (1945/1985) -- The Soviets en route to Nuremberg -- Film as visual documentation at the Nuremberg trials -- The French connection to Nuremberg -- Post-Nuremberg -- Epilogue -- Notes -- Chronology -- Holocaust film bibliography -- Nuremberg trials bibliography -- Filmography